Spatial distribution and risk factors of dengue and Japanese encephalitis virus infection in urban settings: The case of Vientiane, Lao PDR - Julie Vallée (2018)
Objectives To evaluate the prevalence of flavivirus infection in Vientiane city (Lao PDR), to describe the spatial distribution of infection within this city, and to explore the link between flavivirus seroprevalence and urbanization levels of residential neighbourhoods. Methods A seroprevalence survey was carried out in 2006 including 1990 adults (≥35 years) and 1568 children (≥6months and <6 years) randomly selected. Results The prevalence of individuals with previous flavivirus infection (i.e. negative for both DEN and JE IgM but positive for DEN IgG) was 57.7%, with a significantly (P < 0.001) higher prevalence among adults (84.6%; 95% confidence interval (CI) = 82.4-86.8) than children (9.4%; 95% CI = 7.2-11.6). The prevalence of individuals with recent flavivirus infection (i.e. positive for DEN and\or JE IgM) was 6.5% and also significantly (P < 0.001) higher among adults (10.0%; 95% CI = 8.3-11.7) than children (2.5%; 95% CI = 1.5-3.5). In terms of spatial distribution, IgG prevalence was significantly (P < 0.001) higher among individuals living in the central city (60.1%; 95% CI = 56.2-64.1) than among those living in the periphery (44.3%; 95% CI = 41.5-47.2). In contrast, seroprevalence of recent flavivirus infections was significantly (P < 0.001) higher among individuals living in the periphery (8.8%; 95% CI = 6.9-10.7) than in the central city (4.0%; 95% CI = 2.9-5.2). This association was also statistically consistant (P < 0.01) in multivariate logistic regression after controlling for individual risk factors. Conclusions Our findings indicate that the level of urbanization of residential neighbourhoods influences the risk of flavivirus infection. The spatial distribution of flavivirus infection varies, even within a small city of less than 300 000 habitants such as Vientiane. © 2009 Blackwell Publishing Ltd.